2007
DOI: 10.1007/s11606-007-0353-7
|View full text |Cite
|
Sign up to set email alerts
|

Is Information on Genetic Determinants of Obesity Helpful or Harmful for Obese People?—A Randomized Clinical Trial

Abstract: BACKGROUND AND OBJECTIVES: Although more and more genetic information is available, it is unclear whether this information is helpful for patients. Therefore, we assessed the positive and negative effects of informing obese people about the genetic etiology of being overweight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…After receiving information about their genetic status, individuals who tested β3AR-positive were not adversely affected concerning their subjective ability to lose weight or control their eating behavior. In the preliminary analysis of this trial, Rief et al [17] concluded that the inclusion of genetic information is useful for those participants with a familial predisposition for obesity, while the subjective well-being of obese people without a familial predisposition increased if they received a consultation without genetic information. However, in those preliminary analyses, the relevance of weight-related attitudes, weight-related coping, and self-blame about eating was not analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…After receiving information about their genetic status, individuals who tested β3AR-positive were not adversely affected concerning their subjective ability to lose weight or control their eating behavior. In the preliminary analysis of this trial, Rief et al [17] concluded that the inclusion of genetic information is useful for those participants with a familial predisposition for obesity, while the subjective well-being of obese people without a familial predisposition increased if they received a consultation without genetic information. However, in those preliminary analyses, the relevance of weight-related attitudes, weight-related coping, and self-blame about eating was not analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In GWAS, thousands of genes from large numbers of people are linked to different types of phenotypes in order to identify polymorphisms that influence susceptibility to several common chronic diseases [1]. Knowledge about genetic susceptibilities has the potential to transform the practice of medicine by enhancing diagnostic and treatment approaches for common chronic diseases [2]. Although the prospective advantages of GWAS are promising, there are several challenges involved in integrating findings from GWAS into clinical practice [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many GWAS are hypothesis-generating rather than hypothesis-driven, which also raises concerns about replication and lack of validation [11]. Furthermore, results from GWAS may produce findings that indicate increased risk but cannot determine if or when the disease will manifest, as there are low penetrance gene variants [2]. As a consequence, controversy still exists over whether or not it is ethically sound to return genetic research results to individual participants [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Rief and colleagues [31] randomly assigned 294 obese individuals to a weight management consultation either with or without a genetic information component. They also had a no-intervention control group of 116 people.…”
Section: Introductionmentioning
confidence: 99%